The role of MOFs in Thin-Film Nanocomposite (TFN) membranes - Van Goethem, Cédric; Verbeke, Rhea; Pfanmöller, Martin; Koschine, Tönjes; Dickmann, Marcel; Timpel-Lindner, Tanja; Egger, Werner; Bals, Sara; Vankelecom, Ivo F. J. (Journal of membrane science, 2018)
Incorporation of MOFs in interfacially polymerized Thin-Film Nanocomposite (TFN) membranes has widely been shown to result in increased membrane performance. However, the exact functioning of these membranes is poorly understood as large variability in permeance increase, filler incorporation and rejection changes can be observed in literature. The synthesis and functioning of TFN membranes (herein exemplified by ZIF-8 filled polyamide (PA) membranes prepared via the EFP method) was investigated via targeted membrane synthesis and thorough characterization via STEM-EDX, XRD and PALS. It is hypothesized that the acid generated during the interfacial polymerization (IP) at least partially degrades the crystalline, acid-sensitive ZIF-8 and that this influences the membrane formation (through so-called secondary effects, i.e. not strictly linked to the pore morphology of the MOF). Nanoscale HAADF-STEM imaging and STEM-EDX Zn-mapping revealed no ZIF-8 particles but rather the presence of randomly shaped regions with elevated Zn-content. Also XRD failed to show the presence of crystalline areas in the composite PA films. As the addition of the acid-quenching TEA led to an increase in the diffraction signal observed in XRD, the role of the acid was confirmed. The separate addition of dissolved Zn2+ to the synthesis of regular TFC membranes showed an increase in permeance while losing some salt retention, similar to observations regularly made for TFN membranes. While the addition of a porous material to a TFC membrane is a straightforward concept, all obtained results indicate that the synthesis and performance of such composite membranes is often more complex than commonly accepted.
Gesehen am 13.03.2020